Comparative Transcriptome Analysis Provides Insights into the Seed Germination in Cotton in Response to Chilling Stress - Qian Shen (International Journal of Molecular Sciences, 2020)
Gossypium hirsutum L., is a widely cultivated cotton species around the world, but its production is seriously threatened by its susceptibility to chilling stress. Low temperature affects its germination, and the underlying molecular mechanisms are rarely known, particularly from a transcriptional perspective. In this study, transcriptomic profiles were analyzed and compared between two cotton varieties, the cold-tolerant variety KN27-3 and susceptible variety XLZ38. A total of 7535 differentially expressed genes (DEGs) were identified. Among them, the transcripts involved in energy metabolism were significantly enriched during germination based on analysis of Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways, such as glycolysis/gluconeogenesis, tricarboxylic acid cycle (TCA cycle), and glyoxylate cycle (GAC). Results from further GO enrichment analysis show the earlier appearance of DNA integration, meristem growth, cotyledon morphogenesis, and other biological processes in KN27-3 compared with XLZ38 under chilling conditions. The synthesis of asparagine, GDP-mannose, and trehalose and the catabolic process of raffinose were activated. DEGs encoding antioxidants (spermidine) and antioxidase (CAT1, GPX4, DHAR2, and APX1) were much more up-regulated in embryos of KN27-3. The content of auxin (IAA), cis-zeatin riboside (cZR), and trans-zeatin riboside (tZR) in KN27-3 are higher than that in XLZ38 at five stages (from 12 h to 54 h). GA3 was expressed at a higher level in KN27-3 from 18 h to 54 h post imbibition compared to that in XLZ38. And abscisic acid (ABA) content of KN27-3 is lower than that in XLZ38 at five stages. Results from hormone content measurements and the related gene expression analysis indicated that IAA, CTK, and GA3 may promote germination of the cold-tolerant variety, while ABA inhibits it. These results expand the understanding of cottonseed germination and physiological regulations under chilling conditions by multiple pathways.